Influence Analysis Expenditure Zakat, Infak Welfare and Charity Against Muzakki (Studies In Baznas In West Lombok Regency) - Asdiansyuri, Ulfiyani (International Journal of Social and Local Economic Governance, 2016)
The aims of this research is to analyze 1) influence factors of individual characteristics as age, marital status, education, number of dependents, income, and understanding values of religious that owned by muzakki against of spending Zakat, Infak and Sedekah (ZIS), and 2) influence factors of individual characteristics such as age, marital status, education, number of dependents, income, and understanding values of religious that owned by muzakki against muzakki’s welfare through spending Zakat, Infak and Sedekah (ZIS). Estimation techniques using validity, the reliability, classical assumption test and path analysis test. The result shows 1) there are influences such as marital status, education, income and religious values against spending Zakat, Infak and Sedekah (ZIS) by a muzakki, and 2) the effect of age, educqation, number of dependents, income and religious values affect muzakki’s welfare by spending through Zakat, Infak and Sedekah (ZIS). Keywords: Individual Characteristics, ValuesReligious, Zakat expenditures, Infak and Sedekah (ZIS), Welfare Muzakki.